A high activity zinc transporter OsZIP9 mediates zinc uptake in rice. (17th June 2020) - Yang, Meng; Li, Yutong; Liu, Zonghao; Tian, Jingjing; Liang, Limin; Qiu, Yu; Wang, Guangyuan; Du, Qingqing; Cheng, Deng; Cai, Hongmei; Shi, Lei; Xu, Fangsen; et al.
SUMMARY: Zinc (Zn) is an essential micronutrient for most organisms including humans, and Zn deficiency is widespread in human populations, particularly in underdeveloped regions. Cereals such as rice ( Oryza sativa ) are the major dietary source of Zn for most people. However, the molecular mechanism underlying Zn uptake in rice is still not fully understood. Here, we report that a member of the ZIP (ZRT, IRT‐like protein) family, OsZIP9, contributes to Zn uptake in rice. It was expressed in the epidermal and exodermal cells of lateral roots, localized in the plasma membrane and induced during Zn deficiency. Yeast‐expressed OsZIP9 showed much higher Zn influx transport activity than other rice ZIP proteins in a wide range of Zn concentrations. OsZIP9 knockout rice plants showed a significant reduction in growth at low Zn concentrations, but could be rescued by a high Zn supply. Compared with the wild type, accumulation of Zn in root, shoot and grain was much lower in knockout lines, particularly with a low supply of Zn under both hydroponic and paddy soil conditions. OsZIP9 also showed Co uptake activity. Natural variation of OsZIP9 expression level is highly associated with Zn content in milled grain among rice varieties in the germplasm collection. Taken together, these results show that OsZIP9 is an important influx transporter responsible for the take up of Zn and Co from external media into root cells. Significance Statement: Rice is the major dietary source of Zn for most people, but the underlying molecular mechanism of how rice absorbs zinc is still unclear. In this research, we characterized OsZIP9 as the major transporter responsible for zinc uptake in rice. Our work provided new insights in understanding Zn uptake in rice and strategies for improving zinc accumulation.